Geographical indication and “cachaça” quality according to the perception of enjoyers (Research, Society and Development, 2020)
The concept of product quality, from the consumer's point of view, is based on its subjective perceptions. However, in the process of purchasing a product, some quality attributes can be observed, assisting the consumer to make his decision. Among these attributes, seals of geographical indication have been identified as indicators of quality of food products and can be considered by consumers to guide the choice. In order to assess the relevance of quality signs and attributes in the choice of Cachaça, by consumers with a high level of knowledge and a high degree of involvement with the beverage, questionnaires were applied to this audience. The results showed that sensory attributes are the most important parameters for cachaça lovers. However, before tasting the product, factors such as brand, price and marketing are more relevant at the time of purchase. The results showed that geographic origin is not yet a relevant concept for this kind of consumers.